Surface-hydroxylated single-atom catalyst with an isolated Co-O-Zn configuration achieves high selectivity in regulating active species - Zhi-Quan Zhang; Pi-Jun Duan; Chang-Wei Bai; Xin-Jia Chen; Jing Wang; Fei Chen (Nature Communications)
Abstract Single-atom catalysts (SACs) are emerging as potent tools for the selective regulation of active species, offering substantial promise for green and sustainable Fenton catalysis. However, current SACs face limitations due to the specificity of their supports, which only allow selective regulation within certain oxidant systems. This constraint makes targeted regulation across different systems challenging. In response, this study designs a SAC, termed CoSAs-ZnO, featuring surface hydroxylation and an isolated asymmetric Co-O-Zn configuration. This SAC can realize a nearly 100% selective generation of sulfate radicals (SO4 •−) and singlet oxygen (1O2) in peroxymonosulfate (PMS) and peracetic acid (PAA) systems, respectively. Moreover, the PMS-activated system can efficiently treat electron-deficient-dominated and refractory benzoic acid wastewater, achieving 100.0% removal in multiple consecutive pilot-scale experiments. The PAA-activated system facilitates the rapid conversion of benzyl alcohol to benzaldehyde, with a high selectivity of 89.0%. Detailed DFT calculations reveal that the surface hydroxyl groups on ZnO play a critical role in modulating the adsorption configurations of the oxidants, thus enabling the selective generation of specific active species in each system. This study provides insights into the design of SACs for multifunctional applications and paves the way for their deployment in wastewater treatment and high-value chemical conversion.